Peran Komunikasi Keluarga dalam Pembentukan Sikap Sosial Remaja di Desa Mariotengga - Aswandy; Andi Dian Fitriana (Institut Agama Islam Negeri Parepare, 2022)
Communication in a family plays a very important role because in a family, family harmony is determined by whether or not communication within the family is smooth. The aim of this research is to determine the factors that influence family communication in the formation of social attitudes of adolescents in Marioritengnga Village, Marioriwawo District, Soppeng Regency. To find out the role of family communication in the formation of social attitudes of teenagers in Marioritengnga Village, Marioriwawo District, Soppeng Regency. The type of research used in this thesis is qualitative. Meanwhile, this type of research uses qualitative descriptions, where the researcher describes the research object using in-depth interviews. Based on the results of interviews and the author's analysis, it is explained that the forms of social attitudes of teenagers in Marioritengnga Village, Merioriwawo District, Soppeng Regency are 1) resistance, 2) prejudice, 3) impolite language, 4) tolerance, 4) responsibility and 5) appreciative attitude. Meanwhile, for the role of the family in forming the social attitudes of teenagers in Marioritengnga Village, Marioriwawo District, Soppeng Regency, implementing effective communication with children. Parents convey messages that children can understand both verbally and nonverbally. Interpersonal communication between parents and children has an impact on children, when children make mistakes, parents give directions in the form of advice, prohibitions, verbal and nonverbal orders.